Construction of Peer Support Groups in Child Protection Social Work: Negotiating Practicalities to Enhance the Professional Self. Issue 1 (2nd January 2017) - Dempsey, Maria; Halton, Carmel
Abstract : This paper reports on a research project that was developed between a cohort of child protection social workers in the Republic of Ireland and the authors. The focus of the research was on researching participants' experiences of developing peer support groups (PSGs) in child protection social work. Eleven participants formed two PSGs; one group had six participant s, the other had five. This qualitative research study involved focus groups with each of the peer groups at the beginning, middle and end of the 12-month period. Data from the focus groups were analysed using thematic analysis (Braun & Clarke, 2006) . Findings from the research indicate that the organic development of a PSG involves negotiating a range of practicalities which, working together, help to promote reflective practice and to advance the development of the professional self. A number of important and interconnected subthemes emerged within the texts of the focus groups. These included: the establishment of PSGs as a work activity; consideration of logistical matters in forming PSGs; identification of the influence of group dynamics in structuring and negotiating PSGs; PSGs as a conduit for integrating personal and professional values and as a context for facilitating and enabling an increased consciousness of self in practice. Drawing on these findings, the authors consider the implications for integrating PSGs within child protection agency services.